2018
DOI: 10.3390/en12010089
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial-Based Radiative Cooling: Towards Energy-Free All-Day Cooling

Abstract: In the light of the ever increasing dangers of global warming, the efforts to reduce energy consumption by radiative cooling techniques have been designed, but are inefficient under strong sunlight during the daytime. With the advent of metamaterials and their selective control over optical properties, radiative cooling under direct sunlight is now possible. The key principles of metamaterial-based radiative cooling are: almost perfect reflection in the visible and near-infrared spectrum (0.3–3 µm) and high th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 75 publications
0
79
0
Order By: Relevance
“…In addition, the presented results are very promising in application areas of thermal-imaging with labeled-security, and daytime radiative coolers. 12,13,69 However, adaptation of the overall absorption response of the device over thermal infrared region to the atmospheric absorption lines should be fulfilled, which is an present ongoing study.…”
Section: Fabrication and Characterization Of The Metasurface Osr Withmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the presented results are very promising in application areas of thermal-imaging with labeled-security, and daytime radiative coolers. 12,13,69 However, adaptation of the overall absorption response of the device over thermal infrared region to the atmospheric absorption lines should be fulfilled, which is an present ongoing study.…”
Section: Fabrication and Characterization Of The Metasurface Osr Withmentioning
confidence: 99%
“…Metamaterials and their sub-wavelength thick counterparts, metasurfaces, represent a class of synthetic, man-made materials, whose sub-wavelength inclusions offer strong light-matter interactions. Their broad [5][6][7][8][9][10][11][12][13][14][15] or narrow [16][17][18][19][20][21][22][23][24] resonant responses enable the efficient harvesting of the confined radiation by an absorbing layer such as metals, or semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…All-day radiation constitutes a powerful energy-saving method for summer cooling. [19][20][21][22][23][24][25] Recent studies have suggested that introducing light scattering particles/cavities into a polymer matrix can increase passive daytime radiative cooling by reflecting solar radiation. [26][27][28][29] Such materials should be designed to reflect the light in the wavelength (λ) range of ≈0.3-2.5 µm but allow thermal emission into the cold outer space through the atmospheric longwave infrared (LWIR) transmission window (λ ≈ 8-13 µm).…”
Section: Doi: 101002/adma202000870mentioning
confidence: 99%
“…Their proposed metamaterial is an alternating dielectric layers stack, obtained based on hafnium and silicon oxides deposited by evaporation. Other solutions based on metamaterials or porous alumina were developed more recently [24][25][26].…”
Section: Introductionmentioning
confidence: 99%